Antidepressant treatment among social workers, human service professionals, and non-human service professionals: A multi-cohort study in Finland, Sweden and Denmark - O. Rantonen; K. Alexanderson; A.J. Clark; V. Aalto; A. Sónden; H. Brønnum-Hansen; C.Ø. Hougaard; N.H. Rod; E. Mittendorfer-Rutz; M. Kivimäki; T. Oksanen; P. Salo (Elsevier BV, 2022)
Background
Social workers have an elevated risk for mental disorders, but little is known about their antidepressant treatment.
Aims
To examine any and long-term antidepressant treatment among social workers in Finland, Sweden and Denmark.
Methods
We linked records from drug prescription registers to three prospective cohorts: the Finnish Public Sector study, years 2006–2011, and nation-wide cohorts in Sweden and Denmark, years 2006–2014, including a total of 1.5 million employees in (1) social work, (2) other social and health care professions, (3) education and (4) office work. We used Cox proportional hazards models to estimate hazard ratios for any and long-term (>6 months) antidepressant treatment among social workers compared to the three reference occupational groups and carried out meta-analyses.
Results
During follow-up, 25% of social workers had any prescriptions for antidepressants (19–24% reference occupations) and 20% for long-term treatment (14–19% reference occupations). The pooled effects for any and long-term treatment showed that probabilities were 10% higher in social workers compared to other health and social care professionals and 30% higher compared to education and non-human service professionals. Probabilities for any treatment in the three countries were relatively similar, but for long-term treatment social workers in Finland had a greater risk compared with other human service professions.
Limitations
There were differences between the cohorts in the availability of data. Specific diagnoses for the antidepressant treatment were not known neither adherence to treatment.
Conclusion
Social workers have a higher risk for any and long-term antidepressant treatment than other human and non-human service professionals.